Pemahaman Siswa tentang Nilai Eksistensi Perempuan pada Tokoh Raihana dalam Novel Pudarnya Pesona Cleopatra Karya Habiburrahman El Shirazy - Nurul Ulum; Nurrudin Nurrudin; Shafruddin Tadjuddin (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2020)
The purpose of this study was to determine the value of the existence of women from the figure of Raihana in the novel Pudarnya Pesona Cleopatra by Habiburrahman El Shirazy as a wife figure who became the dream of all men, but not for her husband. The research method used is descriptive qualitative. The research data was taken from the reception of class X TKR students of SMK Bina Karya 2 Karawang as primary data obtained from interviews and secondary data were sentences in the novel Fading Pesona Cleopatra. Data analysis uses data classification stages, data analysis according to categories, and conclusions. The results showed that the value of the existence of Raihana figures can be seen from the nature of sholehah, merciful, obedient and not easily discouraged. Raihana has described the figure of a gentle woman in dealing with various problems and attitudes from her husband who were not pleasant. In conclusion, students understand the figure of Raihana as a figure who is very good and has the value of intelligence that is able to provide balance to the husband. Keywords: Values, Existence, Women, Novel